If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(m + 1) = 3(2m + -2) Reorder the terms: 5(1 + m) = 3(2m + -2) (1 * 5 + m * 5) = 3(2m + -2) (5 + 5m) = 3(2m + -2) Reorder the terms: 5 + 5m = 3(-2 + 2m) 5 + 5m = (-2 * 3 + 2m * 3) 5 + 5m = (-6 + 6m) Solving 5 + 5m = -6 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 5 + 5m + -6m = -6 + 6m + -6m Combine like terms: 5m + -6m = -1m 5 + -1m = -6 + 6m + -6m Combine like terms: 6m + -6m = 0 5 + -1m = -6 + 0 5 + -1m = -6 Add '-5' to each side of the equation. 5 + -5 + -1m = -6 + -5 Combine like terms: 5 + -5 = 0 0 + -1m = -6 + -5 -1m = -6 + -5 Combine like terms: -6 + -5 = -11 -1m = -11 Divide each side by '-1'. m = 11 Simplifying m = 11
| rc+rx+bc+bx=0 | | 43+x=6+3x | | 20m^2+25m^3= | | 16+7x=-40 | | 20*20-90+40= | | 5x^2-39x+29=0 | | Z=8(x+h) | | 0.00000458=(x^2)/3.9 | | 4.58*10^-6=[2x]^2/[3.9-x] | | X^2+85x-13800=0 | | 75p^3+50p^2-12p-8=0 | | (w+2)(w^2-3w+4)= | | 4.58*10^-6=(2x)^2/(3.9-x) | | 0.2x+0.3y=8 | | 3x+5x=1 | | 6X^2-10x-44x=0 | | 7/12•1/4=5 | | 9.40=x/(1.78-x) | | 100-0.24= | | 2x-18+x=15 | | 3x-50+8x=1300 | | 7890^1/6 | | B^3-4b^2-4b+16= | | 6x+11-29=732 | | 2/9=t/6 | | 18+5n-9=2n+3 | | (9.40)(1.78-x)=x | | 6x+11x-29=732 | | -12a^5+12a^4-4a^3= | | 10a+6a^3=0 | | 6/35b=36/5 | | -12a^5+8a^4-4a^3= |